Malaysia Youth Council (MBM) and its relevance to youth development - Dahalan, Dzuhailmi; Abdullah, Haslinda; Hamzah, Azimi; Ismail, Ismi Arif; Tamam, Ezhar; Abdullah, Abdul Lateef; Gill, Sarjit S.; Ahmad, Nobaya; Suandi, Turiman (Science Publications, 2012)
Problem statement: Malaysia Youth Council (MBM) which is also known as National Youth Council is a Non-Governmental Organization (NGO) accredited to represent the voice of youth generation in Malaysia. Its main aim is to boost and motivate youth organizations to play a positive and effective role towards society and country. However, does MBM currently being transformed holistically in the true sense as the catalyst of Malaysian youth development? Does MBMs presence being felt by youth in Malaysia completely? Approach: Data for this study were collected based on literature analysis, random observations on the scenario that happened, discussion among fellow researchers in the field of youth development and selective and informal feedback from a number of fellow practitioners that are active in youth work in Malaysia. Results: Analysis found that there are still several outdated issues that need to be resolved especially related to the weakness of the youth organizations in Malaysia, whereby this not reflect the acknowledgement of MBM as the body that fight for the youth concerns in Malaysia. Conclusion: The findings provide space for further research on issues raised from various perspectives apart from empowering Malaysian youth in the near future.